School-Related Social Support Is Associated With School Engagement, Self-Competence and Health-Related Quality of Life (HRQoL) in Turkish Immigrant Students - Demir, Meryem; Leyendecker, Birgit (Frontiers in Education, 2018)
This study examines how school-related social support from teachers and classmates is related to the health-related quality of life (HRQoL), school engagement, and self-competence of Turkish immigrant students in Germany. We used data from the SIMCUR study with a longitudinal and cohort-sequential design. The study included a total of 216 Turkish immigrant children and adolescents. Complete longitudinal data was available for 161 participants. Students rated their perceived teachers and classmate support, HRQoL, school engagement, and self-competence in math and reading in 4th (n = 136), 5th (n = 110), and 6th grades (n = 100) (middle/ M-cohort), or in 7th (n = 73) and 8th (n = 69) grades (older/ O-cohort). Multiple regression analysis revealed that school-related social support had positive effects on all outcomes in 4th grade. In 5, 6, and 7th grades, higher classmate support was associated with higher HRQoL but not with school engagement and self-competence, whereas higher teacher support was associated with higher school engagement and self-competence but not with HRQoL. In 8th grade, only a positive effect of teacher support on school engagement was found. Girls were more likely to report higher school-related social support, but this reached significance only for the M-cohort. Boys in 5, 7, and 8th grades reported higher self-competence in math than girls. We found hardly any effects of maternal education level on HRQoL and school outcomes of students. Only for 4th grade students was higher maternal education level associated with higher school engagement. Our findings indicate that for younger children especially in elementary school, teacher, and classmate support has positive effects on both HRQoL and school-related variables; for students at the beginning of middle school, classmate support only has an influence on HRQoL. Regarding school matters, students in these grades profit from teacher support as from classmates. During adolescence, school-related social support loses significance in terms of HRQoL and self-competence. However, teacher support still seems to have a significant impact on students' school-engagement. From an applied perspective, interventions aimed at HRQoL and academic achievement of children and adolescents should include a focus on social support by teachers and classmates.